Elaboración del manual de procedimientos seguros en la Torre de Precalentamiento de la empresa Cemento Chimborazo C.A - Briones Vizuete, Ximena Carolina (2011)
The present research has as its central theme the construction of a cereal pilot rotary dryer for Unit Operations Laboratory at Faculty of Engineering, which will serve as a great contribution for students are able to make Lab. Practice and they acquire skills to develop in their professional life. The cereal pilot rotary dryer, is heated by an electrical resistance of up Watts in 220 volts, this dryer has a capacity of 5 kilograms, consists of a stainless steel drum of 220 mm in diameter and 800 mm in length, on a slide 2 mm thick. The drum rotation is achieved by means of a ring gear that runs at the same position and a group drive unit gearbox. The construction of certain elements of the cereal pilot rotary dryer requires the use of machinery, instruments, tools, through the operations of the process. In the laboratory practices of different cereals like: corn, peas, beans, beans in them are the statistical tables corresponding to each practice, these will serve as a guide for students and teachers of the Faculty.